2020
DOI: 10.4103/jfmpc.jfmpc_211_20
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe acute malnutrition among children aged 6–59 months: A community-based case-control study from Vellore, Southern India

Abstract: Background: Malnutrition plays an important role in the economic burden of society as well as the country. This study aimed to identify the various risk factors and determinants of severe acute malnutrition (SAM) as defined by WHO growth reference standards in children aged 6 months to 59 months living in Vellore. Methods: A community-based case-control study matched for age (±2months), gender and location was done among the children of the age group 6- 59 months residi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
0
9
4
2
Order By: Relevance
“…Among the family risk factors, age, educational level and BMI of the mother, according to our data, do not seem to be signi cantly associated with childhood malnutrition, although the small number of samples does not allow us to exclude a correlation, which has instead been demonstrated in other studies (7,25).…”
Section: Discussioncontrasting
confidence: 67%
“…Among the family risk factors, age, educational level and BMI of the mother, according to our data, do not seem to be signi cantly associated with childhood malnutrition, although the small number of samples does not allow us to exclude a correlation, which has instead been demonstrated in other studies (7,25).…”
Section: Discussioncontrasting
confidence: 67%
“…Among the family risk factors, age, educational level and BMI of the mother, according to our data, do not seem to be significantly associated with childhood malnutrition, although the small number of samples does not allow us to exclude a correlation, which has instead been demonstrated in other studies [ 7 , 25 ].…”
Section: Discussioncontrasting
confidence: 61%
“…Similar studies by Hasan et al in Bangladesh, Dabar et al in South Delhi, David et al in Vellore and Inkane et al in Nagpur have shown that children of mothers with secondary or higher education were at lower risk of childhood malnutrition when compared with children of mothers with no education. [11][12][13] While taking children birth weight into consideration, it was observed in present study that wasting, stunting and underweight were higher among children who had history of LBW as compared to children with normal birth weight, which is found to be statistically significant (p<0.01). This is due to the fact that, as birth order of child increases, the care given to them decreases, because mothers will have to take care of more number of children, which will have a negative impact on their nutritional status.…”
Section: Resultsmentioning
confidence: 73%
“…Similar findings were observed in the studies conducted by David et al in Vellore, Basit et al in Udupi and Priyanka et al in Maharashtra. [13][14][15][16] In present study children with higher birth order (three or more) or children belonging to a family size of three or more, had higher prevalence of wasting, stunting and underweight. Similar findings were observed in studies of Dabar et al in South Delhi and Gladius et al in Tamil Nadu, where higher birth order was significantly associated with malnutrition.…”
Section: Resultsmentioning
confidence: 83%